2019
DOI: 10.17848/wp19-298
|View full text |Cite
|
Sign up to set email alerts
|

Payroll, Revenue, and Labor Demand Effects of the Minimum Wage

Abstract: We study the impact of the minimum wage hike in Seattle from $9.47 to $13 on wagebill, labor demand, and firm revenue using administrative data from the state of Washington. We show that the minimum wage affected businesses both at the intensive and extensive margins. At the intensive margin, businesses increased their labor costs and adjusted to the minimum wage by mildly reducing demand for low-wage jobs, but they largely did not pass the increase in labor costs to prices. At the extensive margin, the minimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…In-depth interviews with workers, nonprofits leaders, and for-profit employers produced for other parts of the Seattle Minimum Wage Study corroborate survey findings reported here (The Seattle Minimum Wage Study Team 2016, 2017b). Our findings also align with analyses of UI administrative data to assess the impact of the minimum wage ordinance in Seattle (Jardim et al 2017; Jardim and van Inwegen 2017).…”
Section: Limitationssupporting
confidence: 80%
“…In-depth interviews with workers, nonprofits leaders, and for-profit employers produced for other parts of the Seattle Minimum Wage Study corroborate survey findings reported here (The Seattle Minimum Wage Study Team 2016, 2017b). Our findings also align with analyses of UI administrative data to assess the impact of the minimum wage ordinance in Seattle (Jardim et al 2017; Jardim and van Inwegen 2017).…”
Section: Limitationssupporting
confidence: 80%
“…For a detailed analysis of the effect of the Ordinance on firm behavior, seeJardim and van Inwegen (2018).…”
mentioning
confidence: 99%
“…Early UW-MWS work on employment outcomes draw on these UI data (Jardim, Long, Plotnick, van Inwegen, Vigdor, and Wething 2017a, 2017b, 2017cJardim and van Inwegen, 2017). Jardim et al (2017a) finds that the Ordinance prompted a reduction in "hours worked in low-wage jobs by around 9 percent, while hourly wages in such jobs increased by around 3 percent.…”
Section: Washington State Ui Data and Findings To Datementioning
confidence: 99%